2001
DOI: 10.1258/0004563011901172
|View full text |Cite
|
Sign up to set email alerts
|

Immulite 2000 parathyroid hormone assay: stability of parathyroid hormone in EDTA blood kept at room temperature for 48 h

Abstract: SUMMARY. Parathyroid hormone (PTH) concentrations were compared in serum and EDTA plasma from 36 patients attending a renal stone clinic. Serum PTH concentrations ranged from 0·9 to 10·9pmol/L, with a mean of 4·6 pmoljL. When serum and EDT A plasma results were compared, in samples frozen within 30min of collection, EDTA plasma results were found to be significantly higher than those in serum (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 1 publication
2
10
2
1
Order By: Relevance
“…The results presented here confirm previous reports describing higher apparent PTH concentrations in EDTA plasma than in serum (1,2 ) and changes in PTH concentrations with time (1)(2)(3)(4)(5)(6). In agreement with what has been published for the DPC PTH assay (1 ), we found a slight increase in PTH concentration in EDTA plasma with time.…”
Section: Influence Of Preanalytical Factors On the Immulite Intact Pasupporting
confidence: 93%
See 1 more Smart Citation
“…The results presented here confirm previous reports describing higher apparent PTH concentrations in EDTA plasma than in serum (1,2 ) and changes in PTH concentrations with time (1)(2)(3)(4)(5)(6). In agreement with what has been published for the DPC PTH assay (1 ), we found a slight increase in PTH concentration in EDTA plasma with time.…”
Section: Influence Of Preanalytical Factors On the Immulite Intact Pasupporting
confidence: 93%
“…Measured PTH concentrations in EDTA plasma may (1,2 ) or may not (3 ) differ from those in serum. PTH has been reported variously to be stable for hours to days (1)(2)(3)(4)(5)(6). In addition, different PTH assays cross-react to various extents with biologically inactive, N-terminally truncated PTH molecules (7 ) that may have different stabilities.…”
Section: Influence Of Preanalytical Factors On the Immulite Intact Pamentioning
confidence: 99%
“…The two studies using Immulite 2000 6,7 both showed PTH to be higher in EDTA plasma than serum at baseline, whereas our study and that of Levin and Nisbet showed PTH to be slightly lower. There may have also been subtle di¡erences in sample handling and preparation.…”
Section: Discussioncontrasting
confidence: 74%
“…After 3 days of storage, measured PTH concentration in EDTA plasma had not decreased, but had declined by more than 40% in serum. Omar et al, 7 using the Immulite 2000, also observed improved stability in EDTA plasma. However, in their study, PTH concentrations in fresh EDTA plasma were 20% higher than in fresh serum.…”
Section: Discussionmentioning
confidence: 93%
“…Fifteen papers relating to PTH stability in whole blood were identified that had used a second generation assay ( Figure 2, Supplemental Data Table 3) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Collation of study results was difficult due to variation in experimental design (see above), but almost all studies suggested that PTH was more stable in whole blood samples containing EDTA than in anticoagulant-free samples (Supplemental Data Table 3).…”
Section: Stability In Anticoagulated and Clotted Whole Blood At Room mentioning
confidence: 99%